1557. Acyclovir-Resistant (ACV-R) Herpes Simplex Virus (HSV) Disease in Patients with Hematologic Malignancies (HM) and Hematopoietic-Cell Transplant (HCT) Recipients. (26th November 2018) - Pandit, Alisha; Cheng, Matthew P; Liakos, Alexis; Treister, Nathaniel; Baden, Lindsey R; Issa, Nicolas C; Marty, Francisco M; Hammond, Sarah P
Abstract: Background: HSV reactivation is a challenging complication of HM and HCT. ACV prophylaxis effectively decreases the incidence of symptomatic HSV episodes, but may contribute to development of ACV-R HSV disease in this population. Outcomes in patients with ACV-R HSV disease remain poorly characterized. Methods: We identified adult HM patients and HCT recipients treated at Dana-Farber Cancer Institute who developed clinically significant ACV-R HSV disease between January 1, 2006 and March 1, 2018. HCT recipients typically receive 1 year of ACV prophylaxis after HCT, or longer in those with graft-vs. host disease. Clinical, microbiological and treatment details were collected. Results: Nineteen patients had 27 episodes of ACV-R HSV disease during the study. Median age was 50 years (range 31–77); 15 (79%) were men. Fifteen (79%) were allogeneic HCT recipients and 4 (21%) had HM (3 CLL, 1 NHL). Thirteen (68%) had oral ulcers (HSV1), four (21%) had perineal ulcers (3 HSV2, 1 HSV1), one had HSV1 vesicles on the trunk and one had concurrent oral HSV1 and perineal HSV2 ulcers. Three patients had recurrent ACV-R HSV: two had one recurrence each and one had six recurrences. Of 19 first episodes of ACV-R HSV, 15 (79%) were confirmed by culture-based phenotypic resistance testing. Most episodes (20/27, 74%) were treated with foscarnet at clinical diagnosis or after failure of high-dose val-ACV; four of these episodes were also treated with topical cidofovir without success before foscarnet. Three episodes resolved on high-dose val-ACV or IV ACV alone and three were treated with cidofovir or brincidofovir initially. Coinfection was present in 19 episodes (70%), most often bacterial pneumonia or blood stream infection. Twenty-two episodes (81%) resolved completely after a median of 36 days (range 10–88) of treatment. No patient died of HSV disease but five (26%) died before resolution of ACV-R HSV, a median of 25 days (range 1–117) after treatment started. Eight patients died after ACV-R HSV resolved, a median of 111 days (range 27–382) after treatment started. Among HCT recipients, six (37%) died within 12 weeks of diagnosis. Conclusion: ACV-R HSV disease is an uncommon complication of HM and allogeneic HCT. While ACV-resistant HSV did not cause death in this cohort, death within 12 weeks of infection was common. Disclosures: N. C. Issa, GSK: Investigator, Research grant; Merck: Investigator, Research grant; Akros Pharma: Consultant, Consulting fee. F. M. Marty, Chimerix: Consultant and Investigator, Consulting fee and Research support. S. P. Hammond, Merck: Investigator, Research support.